Bendamustine in the treatment of patients with indolent non‐Hodgkin lymphoma refractory or relapse to rituximab treatment: An open‐label, single‐agent, multicenter study in China. Issue 4 (21st December 2022) - Gao, Yan; Liu, Yizhen; Wang, Yafei; Zhang, Qingyuan; Wu, Depei; Ye, Xu; Wu, Jianqiu; Xu, Wei; Zhou, Jianfeng; Yang, Yu; Cen, Hong; Zhang, Feng; et al.
Abstract: Background: The optimal treatment strategy for refractory or relapse (R/R) indolent non‐Hodgkin lymphoma (iNHL) has not been fully identified. This study aims to investigate the efficacy and tolerance of bendamustine hydrochloride developed in native Chinese corporation in the treatment of patients with R/R iNHL. Methods: A total of 101 patients from 19 centers were enrolled in this study from July 2016 to February 2019. Bendamustine hydrochloride (120 mg/m 2 ) was given on days 1 and 2 of each 21‐day treatment cycle for six planned cycles or up to eight cycles if tolerated. Parameters of efficacy and safety were analyzed. Results: The median age of the patients was 53.44 (range, 24.4–74.6) years old. A total of 56 (55.44%) patients completed at least six treatment cycles, and the relative dose intensity was 93.78%. The overall response rate was 72.28%, and the median duration of response was 15.84 months (95% confidence interval [CI], 13.77–27.48 months). Median progression‐free survival was 16.52 months (95% CI, 14.72–23.41 months), and the median overall survival was not reached. Grade 3 or 4 hematologic toxicities included neutropenia (77.22%), thrombocytopenia (29.70%), and anemia (15.84%). The most frequent nonhematologic adverse events (any grade) included nausea, vomiting, fatigue, fever, decreased appetite, and weight loss. Seven patients died during the trial, and four cases may be related to the investigational drug. Conclusions: This study reveals that bendamustine hydrochloride is a feasible treatment option for the indolent B‐cell non‐Hodgkin lymphoma patient who has not remitted or relapsed after treatment with rituximab. All adverse events were predictable and manageable. Abstract : This open‐label, multicenter study demonstrated that bendamustine is a feasible treatment option for indolent B‐cell non‐Hodgkin lymphoma patients in China who have not remitted or relapsed after treatment with rituximab. All adverse events were predictable and manageable.